2007
DOI: 10.1542/peds.2005-0760
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Washing and Diapering Equipment Reduces Disease Among Children in Out-of-Home Child Care Centers

Abstract: Diapering, hand-washing, and food-preparation equipment that is specifically designed to reduce the spread of infectious agents significantly reduced diarrheal illness among the children and absence as a result of illness among staff in out-of-home child care centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 24 publications
0
51
0
2
Order By: Relevance
“…Studies have shown positive changes in health and safety policies (i.e., handwashing practices) in child care centers following general health and safety intervention programs (i.e., child care health consultation in child care centers) (Alkon, Bernzweig, To, Wolff, & Mackie, 2009;Kotch et al, 2007). Qualitative studies of child care health consultation have identified the roles and responsibilities of the child care health consultants who provide the intervention (Alkon, Farrer, & Bernzweig, 2004;Isbell et al, 2013) and the facilitators and barriers to implementing general health consultation in child care (Farrer, Alkon, & To, 2007).…”
mentioning
confidence: 99%
“…Studies have shown positive changes in health and safety policies (i.e., handwashing practices) in child care centers following general health and safety intervention programs (i.e., child care health consultation in child care centers) (Alkon, Bernzweig, To, Wolff, & Mackie, 2009;Kotch et al, 2007). Qualitative studies of child care health consultation have identified the roles and responsibilities of the child care health consultants who provide the intervention (Alkon, Farrer, & Bernzweig, 2004;Isbell et al, 2013) and the facilitators and barriers to implementing general health consultation in child care (Farrer, Alkon, & To, 2007).…”
mentioning
confidence: 99%
“…The study of diapering equipment designed to reduce the spread of infectious agents' was found to significantly reduced diarrheal illness among the children because of decreased illness among staff out-of-home in childcare centers. 17 The impact of the equipment can therefore add value to the impact of training in proper diaper-changing and hand-washing that has been observed in previous studies (Table 3 and 4). Over resourced…”
Section: Discussionmentioning
confidence: 77%
“…16 Behavioural change strategies for reducing diarrhoea in out-of-home childcare, study showed that diapering and hand-washing equipment specifically designed to reduce the spread of infectious agents' significantly reduced diarrheal illness among the children and absence because of decreased illness among staff in out-of-home childcare centers. 17 The study went further to state that, the impact of the equipment can add value to the impact of training in proper diaper-changing and hand-washing that has been observed in previous studies. 17 Additionally, structure, cleanliness, and general outlook of latrines are implicated in the rate of utilization of sanitary facilities by the school children.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Os equipamentos e o treinamento utilizados no grupo que recebeu a intervenção reduziram a veiculação de agentes infecciosos, a ocorrência de diarreia entre as crianças e a ausência no trabalho entre os cuidadores (KOTCH et al, 2007).…”
Section: Sul E O Sudeste Possuidores Dos Melhores Indicadores Educaciunclassified